The Baker Street translation [large type] - Robertson, Michael, 1951- (Thorndike Press, 2013)
When brothers Reggie and Nigel Heath lease law offices at 221B Baker Street in London, they discover that it comes with a unique stipulation: the responsibility of answering mail that arrives for previous resident - Sherlock Holmes. In this smart and charming mystery, an elderly American heiress wants to leave her fortune to Holmes, a translator wants him to explain a nursery rhyme, and media mogul Robert Buxton - Reggie's romantic rival - goes missing.